2017
DOI: 10.3892/ijmm.2017.3219
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin inhibits multi-heavy metal mixture-induced HL7702 cell apoptosis through downregulation of ROS-activated mitochondrial pathway

Abstract: With the rapid economic development in recent years, China is facing a great challenge due to heavy metal pollution. The heavy metals may enter the human body through ingestion of aqua products to cause great health risks. In the present study, the inhibitory effects of luteolin on the combined toxicity of multi-heavy metals (including zinc, manganese, lead, copper, cadmium, mercury, chromium and nickel) were investigated in HL7702 hepatocyte cells. An MTT assay demonstrated that 20 μM luteolin significantly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, seedling roots of L. luteus preprocessing with total flavone extracted from Pb-treated cotyledons exhibit strengthened toleration to heavy metal stress [40]. Luteolin, a common flavonoid, has an inhibitory effect on the toxicity induced by heavy metals [41]. For example, luteolin regulates the redox imbalance, preserves mitochondrial function, and depresses caspase-family-associated apoptosis induced by copper (Cu) [42].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, seedling roots of L. luteus preprocessing with total flavone extracted from Pb-treated cotyledons exhibit strengthened toleration to heavy metal stress [40]. Luteolin, a common flavonoid, has an inhibitory effect on the toxicity induced by heavy metals [41]. For example, luteolin regulates the redox imbalance, preserves mitochondrial function, and depresses caspase-family-associated apoptosis induced by copper (Cu) [42].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have found that Lut effectively ameliorates heavy metal-induced pathological lesions in various organs by enhancing antioxidant enzyme activities and reversing mitochondrial dysfunction [27][28][29]. Moreover, Lut inhibits PARP-1 activation and apoptosis induced by a mixture of heavy metals via reducing reactive oxide species (ROS) levels [30]. Recent studies have reported that the hepatorenal protective effects of Lut involve the activation of SIRT1 and the repair of impaired autophagic flux [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…These processes lead to the accumulation of toxic metabolites in cells. Excessive heavy metals invade the human body, leading to the decrease of mitochondrial number and mitochondrial respiratory chain enzyme activity, eventually the mitochondrial respiratory function 12 . More disadvantageous is that dysfunctional mitochondria can increase the production and release of reactive oxygen species, further aggravating mitochondrial damage 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Excessive heavy metals invade the human body, leading to the decrease of mitochondrial number and mitochondrial respiratory chain enzyme activity, eventually the mitochondrial respiratory function. 12 More disadvantageous is that dysfunctional mitochondria can increase the production and release of reactive oxygen species, further aggravating mitochondrial damage. 13 Therefore, mitochondrial health is particularly crucial for maintaining the normal physiological functions of the kidney.…”
mentioning
confidence: 99%